2014
DOI: 10.1136/bmjopen-2013-004177
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of chlorpyrifos exposure and self-reported neurological symptoms in adolescent pesticide applicators

Abstract: ObjectivesOccupational exposure of organophosphorus pesticides, such as chlorpyrifos (CPF), in adolescents is of particular concern because of the potential vulnerability of the developing neurological system. The objectives of this study were to examine how neurological symptoms reported over the application season vary across time, whether these effects are reversible postapplication and if there are associations between CPF biomarkers and neurological symptoms in an adolescent study population.SettingThe lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
2
47
1
2
Order By: Relevance
“…Although a higher number of symptoms were included in previous surveys, in the presented study, some symptoms which were found to be non-specific or autonomic (e.g. dizziness, headache, nausea, loss of appetite) were excluded, and therefore could not fall under any specific subscale [13,15,16,31]. Data from this study also provided identical findings to those presented by a large US Agricultural Health Study (AHS) on pesticideexposed male farmers [15].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although a higher number of symptoms were included in previous surveys, in the presented study, some symptoms which were found to be non-specific or autonomic (e.g. dizziness, headache, nausea, loss of appetite) were excluded, and therefore could not fall under any specific subscale [13,15,16,31]. Data from this study also provided identical findings to those presented by a large US Agricultural Health Study (AHS) on pesticideexposed male farmers [15].…”
Section: Discussionsupporting
confidence: 73%
“…The survey questionnaire in the current study for the neurological symptoms was based on Swedish Q16 which, in different cultural settings, demonstrated the effects of pesticides on the nervous system among South African women farmers [28], Egyptian agricultural workers [13] exposed to organophosphorus pesticides, in addition to German [29] and Algerian [30] workers exposed to solvents. A modified version of Q16 was validated and used in a large US study on licensed pesticide applicators [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a proportion of the farmworkers categorized suffering from moderate and severe mental disorders in rainy season dramatically increased in dry season (Table 3). The finding of this study was different from the result of a study conducted by Wesseling et al (2010) that found past poisoning with OP was associated with an overall excess of symptoms of psychological distress and a study conducted by [15] …”
Section: Discussioncontrasting
confidence: 56%
“…The toluene extract was then derivatized with BSTFA at 70°C for 1 hour and analyzed by gas chromatography-micro electron capture detection (GC/μECD). Urine specimens were analyzed for TCPy (the detoxified metabolite of CPF) by negative-ion chemical ionization gas chromatography–mass spectrometry, using 13C-15N-3,5,6-TCPy as an internal standard, as described previously (Crane et al, 2013; Farahat et al, 2011; Farahat et al, 2010; Khan et al, 2014). Briefly, samples for TCPy analyses were hydrolyzed with hydrochloric acid, extracted with toluene and derivatized using MTBSTFA.…”
Section: Methodsmentioning
confidence: 99%